Neural network and NLP based chatbot for answering COVID-19 queries. (30th July 2021) - Tiwari, Vishal; Verma, Lokesh Kumar; Sharma, Pulkit; Jain, Rachna; Nagrath, Preeti
During the COVID-19 pandemic, people across the world are worried and are highly concerned. The overall purpose of to study and research was to help society by providing a digital solution to this problem which was a chatbot through which people can at some extent self-evaluate that they are safe or not. In this paper, we propose a chatbot for answering queries related to COVID-19 by using artificial intelligence. Various natural language processing algorithms have been used to process datasets. By artificial neural network, the model is created, and it is trained from the processed data, so that appropriate response can be generated by our chatbot. Assessment of the chatbot is done by testing it with a hugely different set of questions, where it performed well. Also, accuracy of chatbot is likely to increase upon increasing dataset.